PENGARUH PENGEMBANGAN KARIR DAN PROMOSI JABATAN TERHADAP SEMANGAT KERJA KARYAWAN PERUSAHAAN DAERAH AIR MINUM KOTA BENGKULU - Juris Tupadela; Onsardi Onsardi (UM. Bengkulu, 2020)
This study aims to know the effect of Career Development and Job Promotion on the Employee Work spirit of PDAM Kota Bengkulu. This research is a quantitative study with a sample 130 respondents, and uses saturated or census sampling techniques. Data collection techniques used observation and questionnaires. Data analysis techniques used the classic assumption test, multiple linear regression, coefficient of determination (R2), and hypothesis testing. The results showed that the results of multiple linear regression tests using SPSS are Y = -0.720 + 0.438 X1 + 0.342X2. From the results of the hypothesis test found, the Career Development (X1) has a positive effect on the work spirit of PDAM Bengkulu City employees, with the T-test results showing a significance value of 0,000 <0.05. Job Promotion (X2) has a positive effect on employee work spirit in PDAM Kota Bengkulu, with T test results showing a significance value of 0.005 <0.05. The T test and the F test show that career development and promotion have a significant effect on work spirit with a significance level <0.05. This means that Ho is rejected and Ha is accepted. In other words, career development and promotion have a significant effect both partially and jointly on employee work spirit. This is proven by the f test which shows the significance value of 0,000 <0.05. Keywords: Career Development, Job Promotion and Employee Work spirit